Characterization of lymphocyte subsets in ascitic fluid and peripheral blood of decompensated cirrhotic patients with chronic hepatitis C and alcoholic liver disease: A pivotal study. (June 2020) - Romanelli, Roberto Giulio; Vitiello, Gianfranco; Gitto, Stefano; Giudizi, Maria Grazia; Biagiotti, Roberta; Carraresi, Alessia; Vizzutti, Francesco; Laffi, Giacomo; Almerigogna, Fabio
Hepatitis C virus and alcoholic liver disease are major causes of chronic liver diseases worldwide. Little is known about differences between chronic hepatitis C and alcoholic liver disease in terms of lymphocytes' sub-population. Aim of the present study was to compare the sub-populations of lymphocytes in both ascitic compartment and peripheral blood in patients with decompensated liver cirrhosis due to chronic hepatitis C and alcoholic liver disease. Patients with decompensated liver cirrhosis due to hepatitis C virus or alcoholic liver disease evaluated from April 2014 to October 2016 were enrolled. Whole blood and ascitic fluid samples were stained with monoclonal antibodies specific for human TCRɑβ, TCRɣδ, CD3, CD4, CD8, CD19, CCR6, CD16, CD56, CD25, HLA-DR, Vɑ24. Sixteen patients with decompensated liver cirrhosis were recruited (9 with hepatitis C virus and 7 with alcoholic liver disease). In ascitic fluid, the percentage of both CD3 + CD56 − and CD3 + CD56 + iNKT cells resulted higher in hepatitis C virus patients than in alcoholic liver disease patients (1.82 ± 0.35% vs 0.70 ± 0.42% (p < 0.001) and 1.42 ± 0.35% vs 0.50 ± 0.30% (p < 0.001), respectively). Conversely, in peripheral blood samples, both CD3 + CD56 − and CD3 + CD56 + iNKT cells resulted significantly higher in alcoholic liver disease than in hepatitis C virus patients (4.70 ± 2.69% vs 1.50 ± 1.21% (p < 0.01) and 3.10 ± 1.76% vs 1.00 ± 0.70% (p < 0.01), respectively). Both elevation of iNKT cells in ascitic fluid and reduction in peripheral blood registered in hepatitis C virus but not in alcoholic liver disease patients might be considered indirect signals of tissutal translocation. In conclusion, we described relevant differences between the two groups. Alcoholic liver disease patients displayed lower number of CD3 + CD4 + cells and a higher percentage of CD3 − CD16 +, Vα24 + CD3 + CD56 − and Vα24 + CD3 + CD56 + iNKT cells in ascitic fluid than hepatitis C virus positive subjects. Further studies might analyze the role of immune cells in the vulnerability toward infections and detect potential targets for new treatments especially for alcoholic liver disease patients.